KEARIFAN LOKAL DALAM SASTRA MADURA DAN APLIKASINYA DALAM KEHIDUPAN SEHARI-HARI - A. Sulaiman Sadik (IAIN MADURA, 2011)
The change of social structure is indicated by the change of family structure traditional family structure to modern one. Any kinds of family structure need its members knowledge, understanding, loyality bound, and tolerance. This article is about to describe local wisdom found in Madurese literature, particularly how it is applied in daily life. It shows that the member of family must posess knowledge how to manage social life effectively. Furthermore, a family requires a local wisdom to realize it. In brief, knowledge and local wisdom play an importan role in a modern family structure.